The Effect of Tax Avoidance and Financial Distress on Firm Value with Firm Size as a Moderating Variable - Nidha Noer Fauziah; Intan Rahma Sari (CV. ULIL ALBAB CORP, 2026)
This study aims to empirically prove the effect of tax avoidance and financial distress on firm value with firm size as a moderating variable on the LQ45 index listed on the Indonesia Stock Exchange during the period of 2020-2024. This research is quantitative in nature, using secondary data. The sample size was determined using purposive sampling, resulting in a sample of 19 companies and 2 outlier data, for a total sample of 17 companies. The data used in this study was processed using E-views 12. The results showed that tax avoidance and financial distress simultaneously affected firm value. Meanwhile, tax avoidance did not partially affect firm value, while financial distress partially affected firm value. Firm size did not moderate tax avoidance's effect on firm value, but it did moderate and weaken financial distress's effect on firm value.